Pengukuran Indeks Kepuasan Masyarakat (IKM) Pelayanan Kesehatan di Puskesmas Kabupaten Hulu Sungai Utara - Dedie Fahamsyah (Universitas Airlangga, 2018)
Background: To know people's judgment of the services provided by Hulu Sungai Utara public health center (puskesmas) to the public, there should be a measure of the level of people’s satisfaction with health services.Aims: The purpose of this study was to measure the peoples’s satisfaction based on Permenpan RB number 16 in 2014 and measure peoples’s satisfaction based on the Customer Satisfaction Index (CSIndex).Method: This study was observational. There were 13 health centers in Hulu Sungai Utara analyzed. The sample was 450 people who used health services in Hulu Sungai Utara public health centers.Results: The first analysis used the data by Permenpan RB No. 16 of 2014, and the second used the Customer Satisfaction Index (CSIndex). The results of this research based Permenpan number 16 of 2014 found all public health centers in Hulu Sungai Utara had a value of community satisfaction index in either category. By usingCSIndex, it was found that the entire public health centers had a high satisfaction.Conclusions: It can be concluded that the value of Community Satisfaction Index in all public health centres was rather satisfied. Some reconstruction for supporting facilities, such as clean toilet, comfortable and clean waiting room, service information, service flow, management improvement, and product marketing should be done.Keywords: CSIndeks, Community Satisfaction Index, Permenpan, Health Center